Encyclopedia of finance - Lee, Cheng F.; Lee, Alice C.; Gale Group (New York Springer, 2006)
A reference work covering all aspects of finance. Coverage includes finance and statistical applications in finance. For students, professors and researchers.
Electronic reproduction.
Keywords: Finance -- Encyclopedias; Electronic books